If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 4t = 0 Solving 18 + 4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 4t = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 4t = 0 + -18 4t = 0 + -18 Combine like terms: 0 + -18 = -18 4t = -18 Divide each side by '4'. t = -4.5 Simplifying t = -4.5
| 73x+46=119 | | k+27=6(2+k) | | 16p-9q+7p= | | z=6axy | | 2(3u+7)=5(3-2u) | | p=7(2p+4)-11p | | 6s+2s=40 | | -8(2d+6)=2(-12d-16)+4d | | -18=-4x-2x | | n/-8=-2 | | -1=-4x-2x | | -5(-4-n)=-(-10-10n) | | 4r+12/8=5r-10/5 | | 2(2x+2)+2(x+2)=92 | | -28-w=-(6w+8) | | 20/10+4(7) | | -17s=-3(13s+20)+12s | | x/6=x+7/10 | | 5+3x2-10/1+10 | | 5.7q-2.4-5.5q=-0.8q-2.2 | | 20/10+4(7)2 | | 8=y-23 | | 8=3+3x-4x | | 6(2r+3)=40+r | | 3(-w+7)=-(9-3w) | | 11v-4v=21 | | t/-2=0.5 | | 10-10c=-8c-20 | | c^2=-16 | | 18u=-9+19u | | 7=24/x+6 | | -3(19h-12)-5h=-5(15h-2) |